Neuroaesthetic exploration on the cognitive processing behind repeating graphics - Qin, Yuan; Ma, Lan; Kujala, Tuomo; Silvennoinen, Johanna; Cong, Fengyu (Frontiers in Neuroscience, 2022)
Repeating graphics are common research objects in modern design education. However, we do not exactly know the attentional processes underlying graphic artefacts consisting of repeating rhythms. In this experiment, the event-related potential, a neuroscientific measure, was used to study the neural correlates of repeating graphics within graded orderliness. We simulated the competitive identification process of people recognising artefacts with graded repeating rhythms from a scattered natural environment with the oddball paradigm. In the earlier attentional processing related to the P2 component around the Fz electrode within the 150-250 ms range, a middle-grade repeating rhythm (Target 1) did not show difference to a high-grade repeating rhythm (Target 2). However, in the later cognitive processes related to the P3b component around the Pz electrode within the 300-450 ms range, Target 1 had longer peak latency than Target 2, based on similar waveforms. Thus, we may suppose that the arrangement of the repeating graphics did not influence the earlier attentional processing but affected the later cognitive part, such as the categorisation task in the oddball paradigm. Furthermore, as evidenced by the standard deviation wave across the trials, we suggest that the growing standard deviation value might represent the gradual loss of attentional focus to the task after the stimulus onset, and that the zero-growth level may represent similar brain activity between trials.